2020
DOI: 10.1007/s10608-020-10167-4
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Effectiveness of Cognitive Behavioral Therapy in Relieving Nurses’ Ageism Toward Older Adults: A Randomized Controlled Trial

Abstract: Background Although cognitive-behavioral therapy (CBT) techniques are well known for targeting psychological distresses, to date, no study has investigated their effectiveness in relieving death anxiety and ageism among nurses. Methods A parallel randomized controlled trial was conducted according to the CONSORT guidelines during October 2019 at the university hospital. A total of 110 nurses were selected through proportional stratified sampling and randomly assigned to the experimental and control groups. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 52 publications
(64 reference statements)
0
16
0
1
Order By: Relevance
“…Aging sexual stigma may result in a lack of sexual health care for older adults [32]. Nevertheless, cognitive behavioral therapy has been shown to reduce ageism among health care providers [33].…”
Section: Ageism and Adverse Outcomesmentioning
confidence: 99%
“…Aging sexual stigma may result in a lack of sexual health care for older adults [32]. Nevertheless, cognitive behavioral therapy has been shown to reduce ageism among health care providers [33].…”
Section: Ageism and Adverse Outcomesmentioning
confidence: 99%
“…Ageism interventions were mostly intergenerational interventions [25,27,35,36], educational programmes [30][31][32]37] and interventions that included both educational and intergenerational contact components [28,29,33]. We also found cognitive behavioural therapy [34].…”
Section: Results From the Literature Review Of Ageism Programmesmentioning
confidence: 85%
“…Ageism intergenerational interventions demonstrated a significant effect on negative stereotypes about ageing [25][26][27][28][29], attitudes [25,[30][31][32][33][34][35], positive behaviour towards older adults [30], knowledge [33], comfort [35], aging anxiety [27,28], death anxiety [34] and well-being in older adults [26], but no significant effects on working with older adults [30] or in affective attitudes toward older adults [28] were found. Although the Intergenerational Artistic Installation of Madrigal et al [36] found an improvement in younger adults' attitudes toward older adults, but not in younger adults' attitudes toward aging.…”
Section: Results From the Literature Review Of Ageism Programmesmentioning
confidence: 99%
“…However, it is known that negative ageist attitudes can lead to lower quality of care (Heyman et al, 2020) as well as increased burnout and decreased job satisfaction among care staff (Pekcetin, 2018a). Thus, researchers combat ageism with different methods such as cognitive behavioural therapy (Rababa et al, 2020) or nostalgia (Turner et al, 2018). Therefore, it is important to examine whether training can bring about favourable changes in ageist attitudes.…”
Section: Discussionmentioning
confidence: 99%